National Evaluation of the Demonstration to Improve the Recruitment and Retention of the Direct Service Community Workforce - Engberg, John (RAND Corporation, 2009)
Direct service workers (DSWs) provide personal care or nonmedical services to individuals who need assistance with activities of daily living. Direct service work is low-paying and very physically and emotionally demanding, and turnover rates among DSWs are high. In 2003-2004, the Centers for Medicare and Medicaid Services funded ten efforts to increase recruitment and retention among DSWs. This volume evaluates these efforts.